Adaptive Grouping Weapon-Target Assignment with Field-of-view Angle Constraint. Issue 3 (2022) - HuangFu, Yilun; Fan, Yonghua; Li, Guofei; Li, Chenlu
Abstract: The problem of weapon-target assignment for intercepting multiple targets is considered with adaptive grouping and field-of-view angle constraints. In view of the factors influencing the assignment efficiency, the interception probability is evaluated by the criterion indexes of intercepting angle, relative distance, relative speed and required acceleration. A weapon-target assignment method is proposed to achieve effective interception for all targets and avoid over-allocation of missiles. The genetic algorithm with elite retention strategy is used to solve the optimal allocation problem in cosideration of adaptive grouping and field-of-view angle constraints. The simulation results for multi-to-multi assignment verify the proposed strategy with the satisfactory performance.